2021
DOI: 10.1088/1361-665x/ac221a
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of surface textured sensing skin for fatigue crack localization and quantification

Abstract: The timely discovery and monitoring of fatigue cracks in steel structures is an important task in order to ensure structural integrity. However, off-the-shelf strain sensors are small and their deployment is too spatially localized to successfully locate new crack formation or growth within acceptable confidence. A solution is the use of large-area electronics capable of covering large surfaces. The authors have previously developed a sensing skin technology based on a soft elastomeric capacitor (SEC) that con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 40 publications
(51 reference statements)
1
12
0
Order By: Relevance
“…where ν 0 is Poisson's ratio for the SEC, and λ 0 is the SEC's gauge factor In this paper, a gauge factor of 1.7 was used, experimentally validated in Liu et al [20]. If ε m is the strain on the monitored surface:…”
Section: Electromechanical Modelmentioning
confidence: 99%
“…where ν 0 is Poisson's ratio for the SEC, and λ 0 is the SEC's gauge factor In this paper, a gauge factor of 1.7 was used, experimentally validated in Liu et al [20]. If ε m is the strain on the monitored surface:…”
Section: Electromechanical Modelmentioning
confidence: 99%
“…The performance of the sensor at detecting and quantifying fatigue cracks was examined on C(T) specimens. The experimental test was conducted by following the same procedure as in prior work [31]. Figure 2(d) shows the overall experimental setup.…”
Section: Fatigue Crack Testmentioning
confidence: 99%
“…Figure 4(d) shows the simulated maximum principal stress distributed on the welded specimen, where it can be observed that high stress is concentrated along the edge of the welds consistent with the crack propagation path. The fatigue behavior in the numerical simulation is dominated by Paris' law, and the simulation of the fatigue crack growth behavior on the welded specimen was conducted by following the same procedure used in prior work [30], where the separating morphing and adaptive re-meshing technology crack growth simulation tool was used, and 40 face nodes were uniformly assigned on the top and bottom crack faces, as presented in the onset Figure 4(e) presents the normal elastic strain distribution on the cSEC installed at the bottom corner, while figures 4(f) and (g) are the front section views of the sensor installed in the top and bottom corners showing the deformation of the sensors under angular motion. The cSEC's signal can be simulated by extracting the initial area A p,q 0 and the area after deformation A p,q of each mesh element from the FEM to compute the deformed area ∆A p,q , and substituting them into the FE based algorithm (equation ( 17)) to obtained the numerical capacitance response.…”
Section: Numerical Modelmentioning
confidence: 99%
“…It is fabricated by infilling titania (TiO 2 ) and carbon black (CB) particles into a styrene-ethylene-butylene-styrene (SEBS) block copolymer matrix to form the dielectric layer and conductive plates, respectively, and layering them into a sandwiched structure. Notably, the cSEC technology has been characterized and demonstrated for in-plane fatigue crack monitoring and out-of-plane angular motion sensing [30,31]. Compared to conventional strain sensors such as foil gauges, the cSEC covers and senses over large areas and can thus be used to discover new cracks instead of being exclusively used to monitor existing damage.…”
Section: Introductionmentioning
confidence: 99%